2D distribution of Pseudomonas fluorescens activities at the soil-root interface of sunflower grown on vineyard soils: Effects on copper uptake. (December 2021) - Randriamamonjy, S.; Mouret, A.; Metzger, E.; Gaudin, P.; La, C.; Capiaux, H.; Launeau, P.; Giraud, M.; Cornu, J.Y.; Lebeau, T.
Abstract: Pseudomonas fluorescens is a siderophore producing bacteria that is expected to alter the mobility and bioavailability of Cu in vineyard soils due to its ability to produce pyoverdine under iron deficiency. In this study, we monitored the effect of this bacterial species, particularly the production of siderophore, on the mobility and bioavailability of copper (Cu) and other elements using a spatialized approach. Two vineyard soils cultivated with sunflower, one non-carbonated (N-Carb) and one carbonated (Carb), were bioaugmented with P. fluorescens or not. 2D mapping using diffusive equilibration in thin films (DET) and diffusive gradient in thin films (DGT) was performed on day 15 after germination. At the end of the experiment, elements concentrations were measured in the plants and in the soil extracts (CaCl2 0.01 M). The results showed that the mobility of Cu and other elements (Fe, Al, Mn, Zn, N and P) was enhanced in both soils when bioaugmented. The chemistry of DET and DGT provided insights into the processes behind mobility, such as the presence and distribution of free metallophore spots (2–3.5 μM), interpreted as pyoverdine, which played a non-negligible role in Cu, Fe, Al mobilization and to a lesser extent in that of Mn, whereas pH played a limited role. DGT imaging showed that, depending on the speciation of metals in the soil solution, the increase in mobility measured by DET did not always increase bioavailability. Nevertheless, the concentration of copper in the aerial part of sunflower cultivated on the bioaugmented carbonated soil increased by 30% and copper content by 200%. These results identify bioaugmentation with P. fluorescens as a potential way to increase Cu phytoextraction, especially in carbonated soil, mainly because of its effect on plant growth but also on Cu bioavailability at the soil-plant interface. Highlights: Mobility of Cu, Fe, Al, Mn, Zn, N, P enhanced in soils with Pseudomonas fluorescens . Cu concentration (content) in plant increased by 30% (200%) with bioaugmentation. DET-mapping revealed spots of siderophores in the rhizosphere of carbonated soil. Performance in bioaugmentation-assisted phytoextraction higher in carbonated soil. Increase in mobility (DET) did not always lead to an increase in bioavailability (DGT).